The Regulatory Reform of Advocate Organizations in Proposing Oath of Prospective Advocates in Indonesia - Solikin, Nur; Rohmatullah, Anis (University of Jember, Indonesia, 2022)
Following the enactment of Advocate Law 18/2003, Indonesian Bar Association must commence a proposal for the advocate's oath before the High Court. As per the rules, the oath should be submitted by a single bar, whereas there has been more than one advocate association in Indonesia. Each association has claimed to be a legitimate